Effects of Different Relative Humidities on the Corrosion of the Epoxy-Coated Galvanized Steel in the Presence of Sulfur Dioxide - Yildiz, Resit; Dehri, Ilyas (Asian Journal of Chemistry, 2013)
The effects of sulfur dioxide on the atmospheric corrosion of epoxy-coated galvanized steels exposed to different relative humidity was investigated using electrochemical impedance spectroscopy, anodic polarization curves and linear polarization resistance measurement techniques. Measurements were performed on samples that had been tested using an accelerated atmospheric corrosion test. The samples were exposed to sulfur dioxide gas in an atmospheric corrosion test cell that was adjusted to different relative humidities. The results indicate that the coating performance varies with relative humidity. Epoxy-coated samples exposed to relative humidities of 70 and 80 % experienced no degradation, whereas the samples significantly lost their protection behaviour under relative humidities of 90 and 100 %.